Pemasangan Safety Sign di RT 21 Kelurahan Baru Tengah - Rahayu Sri Waskitoningtyas; Tegar Frendianto (Abdimas Universal, 2024)
In order to increase the safety and comfort of visitors in the RT 21 Baru Tengah Subdistrict area, the Community Service Program (KKN) has installed a Safety Sign at the RT 21 location. This safety sign was designed with aesthetic considerations so that it is in harmony with the local natural beauty but still ensures its main function as a safety guide and warning. This service aims to show how installing safety signs can provide information and increase awareness of local residents regarding potential dangers. The methods used include observation, questionnaires and interviews with visitors and area managers. The results of the service show that the majority of visitors feel safer and receive sufficient information from the safety signs that are installed. However, some locations still need improvement in terms of visibility and more detailed explanations. As a recommendation, regular maintenance and re-evaluation of the placement and design of safety signs is needed so that they remain relevant to the conditions and developments in the area.